(untitled) (Journal of University Teaching and Learning Practice, 2026)
Students are coming to university from non-traditional backgrounds and have substantial caring and work commitments. Our university recently introduced an extension policy that enables students to access a no-questions-asked, automatic 7-day extension on a single assessment item for each subject they enrol in. There is no requirement for students to provide a reason or supporting documents, or for academic approval. The aim of this study was to explore the value and impact of the extension policy from the perspectives of students and academic staff. In 2024, 19,469 students accessed at least one automatic 7-day extension. The most common enrolment type was undergraduate students studying part-time (41% of all students enrolled). This group had a significant increase in success rate across 2024 if they accessed the extension (6%, P<0.0001). Students (n=501) and academic staff (n=96) completed a survey. Students highlighted the advantages in reducing stress and helping to manage work-study-life balance. Students also appreciated that they did not need to disclose any personal circumstances. The main reasons that students provided for accessing the extension was to manage work demands and to manage stress, neither of which were reasons permissible using the formal extension policy. One student summarised the policy as ‘an intelligent response to the “modern student”’. Feedback from academic staff was polarising, with many highlighting the challenges of the extension policy, particularly on academic workload and negative impacts on student accountability. The academic staff who were in favour of the extension policy appreciated the need for enhanced flexibility.